(untitled) (Perner’s Contacts, 2010)
The contribution deals with an importance of the human factor as a determinant of special events related to transport of dangerous goods. It notes major weaknesses in the handling and in the transport of dangerous goods. The paper provides the basic legal standards for planning and implementing transport. It presents some results of checks on the transport of dangerous goods on roads in Slovakia.